Effectiveness of the LigaSure Small Jaw Vessel-Sealing System in Hepatic Resection - Yoshimoto, Miwa (Tottori University Faculty of Medicine, 2014)
BACKGROUND: In hepatic resection for liver tumors, reducing operation time and blood loss are important for postsurgical complication prevention. This study aimed to compare the safety and efficacy of the LigaSure Small Jaw (Covidien, Boulder, CO) with those of the Cavitation Ultrasonic Surgical Aspirator (CUSA) system (Integra Life Sciences, Plainsboro, NJ) in hepatic surgery. METHODS: We enrolled 102 patients with liver tumors, of whom 51 underwent liver resection with the CUSA (CUSA group) between March 2004 and April 2011. Another 51 underwent resection with the LigaSure Small Jaw (LS group) between June 2011 and July 2012. We stratified patients by time period depending on the instrument used, and compared operative duration; intraoperative bleeding; and postoperative liver function and complication rate. RESULTS: Total operation time (mean ± SD) was significantly shorter in the LS group than in the CUSA group (358.8 ± 91.7 versus 460.6 ± 146.1 min, P < 0.001). Blood loss was not significantly different between the 2 groups. Frequency of postoperative complications was lower, but not significantly, in the LS group. CONCLUSION: The LigaSure Small Jaw may allow a shorter total operative duration than the CUSA device.